Działalność Działu Informacyjno-Bibliograficznego Książnicy Beskidzkiej w Bielsku-Białej (PDF 1,54 MB) (Książnica Śląska, 2025)
The text briefly presents the history of libraries and reading in Bielsko--Biała and the activities of the Beskid Library in disseminating knowledge about the region. The article shows some databases createdby the library, such as: Beskidzkie ABC, Datownik Regionalny andRegio-sources. It also describes the history of regional bibliographyand the current state of work on this publication initiated in the 1960s.